Diagnosis and surgical management of pulmonary artery sling: a case report - Yurtsever, İsmail; Otçu Temur, Hafize; Yozgat, Can Yılmaz; Erol, Ahmet Berk; Doğuş Kuş, Hazar; Talebazadeh, Faraz; Yozgat, Yılmaz (My University, 2024)
[Abstract Not Available]
Keywords: Pulmonary Artery; Cardiovascular Radiology; Interventional Radiology